PROPOSTA DE APLICAÇÃO DA MANUTENÇÃO CENTRADA EM CONFIABILIDADE NOS EQUIPAMENTOS DE TERMINAIS TERRESTRES E OLEODUTOS DE DISTRIBUIÇÃO DE PETRÓLEO E DERIVADOS - Correa, Marcelo Leal (2012)
The importance of maintaining high reliability and operational availability of equipment has assumed great importance in the petroleum industry, because this has been crucial to the survival of businesses concerning aspects of competitiveness. This occurs because of the constant need for optimization of resources, to enable a sustainable living in the current economic and social development. Thus, this study presents a case study using the methodology for management called Reliability Centred Maintenance RCM. This aims to ensure the provision of information necessary to define a better strategy to develop plans for preventive and predictive maintenance for equipment and tools belonging to the Onshore Terminals Storage and Transport of Oil Pipelines and Products. The RCM, despite coming from and has duly disseminated in the aviation industry, has been adapted by other industries and the purpose of this dissertation is to adapt the same for the industrial oil. To help analyze this context, It was realized an extensive review of literature, bibliograph and scientific search for the management methodology proposed in order to allow a better understanding of its application in maintenance. Aditionally are discussed the phases of implementation of RCM that comes from planning and training of the working group that will enforce it through the selection of systems to be included in the study, analysis of functional failures of equipment, and the development of Failure Mode, Effects and Criticality Analysis - FMECA, technical risk analysis introduced in the RCM methodology. Finally, the study presents a new planning model for preventive maintenance of equipment and instruments for the equipment defined in the study, as well as concluding comments regarding the contribution of the subject and the questions asked and the objectives proposed in this dissertation. It is expected however that the implementation of the methodology allows an improved reliability and system availability that operational unit, besides serving as a suggestion for future application of the technique in other terminals and pipelines.